Likelihood of suffering from an eating disorder in a sample of Spanish cyclists and triathletes - Muros, J. J.; Ávila-Alche, Á.; Knox, E.; Zabala, M. (Journal of Eating Disorders, 2020)
Background: During recent years, there has been increasing interest in the study of eating disorders within sports practitioners, with prevalence being reported to be higher than in the general population. The aim of this study was to describe and predict eating disorders according to sex, body mass index, age and sport discipline within a sample of athletes. Methods: A sample of 4037 cyclists and triathletes from across Spain was selected. Athletes self-reported demographic characteristics and completed the revised restraint scale, SCOFF questionnaire and Mediterranean diet adherence screener. To be eligible for inclusion, participants had to be over eighteen years old. Results: Males were significantly less likely than females (p < 0.001; OR = 0.33), and triathletes (p < 0.01; OR = 0.76) were less likely than cyclists to suffer from an eating disorder. Possibility of suffering from an eating disorder increased with increasing body mass index (p < 0.001; OR = 1.38) and decreasing age (p < 0.001; OR = 0.97). Conclusion: Findings suggest that the roles of sex, sport discipline, age and body mass index predict risk factors for eating disorders in a sample of Spanish athletes. Clinical diagnosis seems necessary to better understand the factors and mechanisms at play when Spanish athletes develop an eating disorder.